2021
DOI: 10.1111/fwb.13714
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of biodiversity metrics by environmental DNA metabarcoding compared with visual and capture surveys of river fish communities

Abstract: Information on α‐ (local), β‐ (between habitats), and γ‐ (regional) diversity is fundamental to understanding biodiversity as well as the function and stability of community dynamics. Methods like environmental DNA (eDNA) metabarcoding are currently considered useful to investigate biodiversity. We compared the performance of eDNA metabarcoding with visual and capture surveys for estimating α‐ and γ‐diversity of river fish communities, and nestedness and turnover in particular. In five rivers across west Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…These numbers were higher than those from the same 22 rivers (159 fish species and 10 red‐listed species; the sum of species from two recent surveys at the nearest site to each river mouth except the Yamato River, which had only one survey) collected by conventional methods (Ministry of Land, Infrastructure, Transport & Tourism, 2021 ). Our results support previous reports that indicated that the eDNA metabarcoding method is more effective than conventional sampling methods, particularly for red‐listed species (Deiner et al., 2016 ; Doi et al., 2021 ; Nakagawa et al., 2018 ; Stoeckle et al., 2017 ). Mugil cephalus and Tridentiger spp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These numbers were higher than those from the same 22 rivers (159 fish species and 10 red‐listed species; the sum of species from two recent surveys at the nearest site to each river mouth except the Yamato River, which had only one survey) collected by conventional methods (Ministry of Land, Infrastructure, Transport & Tourism, 2021 ). Our results support previous reports that indicated that the eDNA metabarcoding method is more effective than conventional sampling methods, particularly for red‐listed species (Deiner et al., 2016 ; Doi et al., 2021 ; Nakagawa et al., 2018 ; Stoeckle et al., 2017 ). Mugil cephalus and Tridentiger spp.…”
Section: Discussionsupporting
confidence: 91%
“…Owing to the development of eDNA metabarcoding, the number of eDNA studies assessing estuarine biodiversity has rapidly increased worldwide (e.g., Goutte et al., 2020 ; Schwentner et al., 2021 ; Stoeckle et al., 2017 ). Although the eDNA approach is particularly advantageous for detecting inconspicuous or low‐abundance threatened species (Sigsgaard et al., 2015 ; Thomsen et al., 2012b ; Wilcox et al., 2013 ), most eDNA metabarcoding studies on the diversity of fish species have not focused on threatened species and have generally been restricted to a few stream locations (Ahn et al., 2020 ; Doi et al., 2021 ). Kume et al.…”
Section: Introductionmentioning
confidence: 99%
“…DNA metabarcoding is a common and widely used technique in microbial diversity studies. DNA metabarcoding for environmental DNA in water (eDNA metabarcoding, ( Taberlet et al, 2012 )) has exploded in recent years as a simple and powerful method for assessing and monitoring aquatic biodiversity including microbes ( Yamamoto et al, 2017 ; Leduc et al, 2019 ; Miya, Gotoh & Sado, 2020 ; Antich et al, 2021 ; Doi et al, 2021 ; Gehri et al, 2021 ). Studies on eDNA metabarcoding include methodological considerations of experimental procedures and processes, such as sampling and DNA extraction methods ( Hermans, Buckley & Lear, 2018 ; Doi et al, 2019 ); Coutant et al, 2021 ; Mathon et al, 2021 ), as well as those applied to monitoring in various taxonomic groups and ecosystems ( Leduc et al, 2019 ; Ruppert, Kline & Rahman, 2019 ; Mathieu et al, 2020 ; Tsuji et al, 2019 ; Antich et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater ecosystems to which eDNA metabarcoding has been applied are rivers, lakes, ponds, and wetlands ( e.g. , McKee et al, 2015 ; Deiner et al, 2016 ; Khomich et al, 2017 ; Antich et al, 2021 ; Doi et al, 2021 ; Gehri et al, 2021 ). Although they differ in the presence or absence of constant water flow, there are no examples of how these habitat types affect fungal DNA extraction.…”
Section: Introductionmentioning
confidence: 99%
“…DNA metabarcoding is a common and widely used technique in microbial diversity studies. DNA metabarcoding for environmental DNA in water (eDNA metabarcoding, Taberlet et al 2012) has exploded in recent years as a simple and powerful method for assessing and monitoring aquatic biodiversity including microbes (Yamamoto et al, 2017; Leduc et al 2019; Miya, Gotoh & Sado, 2020; Antich et al, 2021; Doi et al, 2021; Gehri et al, 2021). Studies on eDNA metabarcoding include methodological considerations of experimental procedures and processes, such as sampling and DNA extraction methods (Hermans et al 2018; Doi et al, 2019; Coutant et al, 2020; Mathon et al, 2021), as well as those applied to monitoring in various taxonomic groups and ecosystems (Leduc et al 2019; Ruppert, Kline & Rahman, 2019; Mathieu et al, 2020; Tsuji et al, 2020; Antich et al, 2021).…”
Section: Introductionmentioning
confidence: 99%